ADAPTASI KEMANDIRIAN WANITA PENYANDANG DISABILITAS TUNA DAKSA DIKOTA PEKANBARU - Nisa Muharany; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Different physical features for people with physical disabilities from normal people in general make a person with physical disabilities a minority. Even so, however, women with disabilities still need to be confident in general to be able to live a life without being dependent on others. The question in this study is How do women with disabilities adapt in efforts to be independent in the city of Pekanbaru and what the types of independence of women with disabilities are.The goal of this research is to find out how the adaptation of women with disabilities in efforts to be independent as well as identify the types of independence of women with physical disabilities. Survey research was the technique used to determine the sources used. On the background of these conditions, 7 informants were identified as subjects of research on the independence of women with disabilities in Pekanbaru Area. The theory used in this analysis is the theory of adaptation by Robbert K. Merton and the theory of Independence by Havighurst. The results of this study are that like normal humans in general, women with disabilities still have to adapt to the goals and methods that have been set to achieve independence so that they do not depend on the people around them. Starting from adaptation to physical conditions, with their social environment and values and habits. Until the last adaptation, namely rebellion due to disagreeing with predetermined goals and methods. Meanwhile, the independence of women with disabilities is described by the ability to accept conditions, be able to interact and work according to ability as a sense of responsibility and are able to make decisions and be responsible for the decisions that have been taken. Keywords: Adaptation, Independence, Women with Disabilities